Calculation of Power Losses for SiC MOSFET Based 3-Phase 3-Level T-Type Inverter - Deniz, Erkan; Turan, Berkan (MUSA YILMAZ, 2025)
In recent years, interest in highly efficient and compact power converters in power electronics applications has been increasing day by day. In this study, a SiC MOSFET-based 3-level (3L) T-Type inverter (TNPC) is proposed to obtain a high-efficiency and compact converter. Considering the MSCSM120HRM163AG-SiC-MOSFET intelligent power modules (IPM) developed by Microchip for 3L T-Type inverter, the power losses of a 3-phase 3-level T-Type inverter are calculated in MATLAB environment. To demonstrate the efficiency of SiC MOSFET based T-Type Inverter, a 3-phase 3L T-Type inverter feeding a vector-controlled 3-phase PMSM is simulated using MATLAB/Simulink and Simscape blocks. In the simulation, the PMSM is operated at different speed references under almost full load (42.09 Nm). While the PMSM operates at 3000 rpm under 40Nm load, the voltage-current waveforms of the SiC MOSFETs in the T-Type inverter are obtained. Using these waveforms and the data from the data sheets of the IPMs, the power losses of the 3L TNPC inverter are calculated for different switching frequencies. The Space Vector PWM method used to generate 50 kHz PWM signals for the 3L T-Type inverter also ensures that the dc-link capacitor voltages remain balanced. In addition, the variations of line-to-line voltage and dc-link capacitor voltages of the inverter and the variations of speed, torque, rotor position, d-q currents, and stator currents of the PMSM are given.
Keywords: Electrical Engineering (Other); Elektrik Mühendisliği (Diğer)